Contrastive Video Examples in Teacher Education: A Matter of Sequence and Prompts - Wilkes, Theresa; Stark, Lisa; Trempler, Kati; Stark, Robin (Frontiers in Education, 2022)
Everyday teaching requires teachers to deal with a variety of pedagogical issues, such as classroom disruptions. Against the background of on-going calls for an evidence-informed practice, teachers should ground their pedagogical decisions not only on subjective theories or experience-based knowledge but also on educational theories and empirical findings. However, research suggests that pre- and in-service teachers rather refer to experiential knowledge than to educational knowledge when addressing practical, pedagogical issues. One reason for the infrequent use of educational knowledge is that acquired knowledge has remained inert and cannot be applied to complex situations in practice. Therefore, implementing learning with contrastive (i.e., functional and dysfunctional) video examples in teacher education seems promising to promote pre-service teachers’ acquisition of educational knowledge. The 2×2-intervention study (N = 220) investigated the effects of the video sequence (dysfunctional-functional/functional-dysfunctional) and of video analysis prompts (with/without) on learning outcomes (concept knowledge, application knowledge) and on learning processes (written video analyses). Results revealed that the sequence dysfunctional-functional led to higher application knowledge in the post-test. There was no sequencing effect on concept knowledge. Prompted groups showed higher concept knowledge and application knowledge in the post-test. Furthermore, both experimental factors affected learning processes, which resulted in higher learning outcomes. In conclusion, learning with contrastive video examples in teacher education seems to be more effective if the video examples are presented in the sequence dysfunctional-functional and if instructional prompts guide the video analysis. The results substantiate the relevance of instructional guidance in learning with video examples and broaden the scope of validity of the concept of learning from errors.